The natural history of preterm premature rupture of membranes in twin pregnancies. (3rd August 2017) - Kibel, Mia; Barrett, Jon; Tward, Carly; Pittini, Alex; Kahn, Michael; Melamed, Nir
Abstract: Objective : To compare the characteristics of preterm premature rupture of membranes (PPROM) between twin and singleton pregnancies. Methods : This was a retrospective study of all women with twin and singleton pregnancies admitted with PPROM between 24–34 weeks of gestation. Results : Overall 698 women with PPROM were eligible for the study: 101 (14.5%) twins and 597 (85.5%) singletons. Twins presented with PPROM at a more advanced gestational age compared with singletons (29.1 ± 2.7 vs. 28.5 ± 2.8 weeks, p  = 0.03). The latency period was shorter in twins compared with singletons, especially for women presenting after 28 weeks of gestation (5.0 ± 0.8 vs. 7.0 ± 0.4 days, p  = 0.01). Women with twins were more likely to deliver within 48 h (OR: 2.7; 95%CI: 1.7–4.2) and were less likely to deliver within 2–7 days (OR:  0.5; 95%CI: 0.3–0.9) following PPROM. The rate of clinical chorioamnionitis or placental abruption following PPROM was lower in twins compared with singletons (15.8% vs. 26.0%, p  = 0.03). Conclusions : PPROM in twin pregnancies tends to occur at a more advanced gestational age, is associated with a shorter latency period and is less likely to be complicated by chorioamnionitis or placental abruption compared with singletons. This information may be useful for counseling and management decisions in cases of PPROM in women with twins.